Effect of electronic structure of energy transfer in bimetallic Ru(ii)/Os(ii) complexes. Issue 4 (5th January 2023) - Dai, Weijun; Yu, Shiwen; Kong, Ci; Zhao, Defang; He, Chixian; Liu, Zining; Dong, Jianwei; Liu, Jian-Jun; Cheng, Feixiang
Abstract : Asymmetric Os(ii )/Ru(ii ) dinuclear complexes exhibit photo-induced intramolecular energy transfer from the Ru-based higher-energy 3 MLCT state to that of the Os-based unit at lower energy. Abstract : Novel monometallic (μ-LL′)Ru, Ru(μ-LL′), homobimetallic Ru(μ-LL′)Ru, and heterodimetallic Ru(μ-LL′)Os and Os(μ-LL′)Ru complexes based on two asymmetrical ligands LL′ (where LL′ = L 1 L 1′, L 2 L 2′ ) have been synthesized and characterized. Spectroscopic analysis indicates that all complexes exhibit intense spin-allowed ligand-centered (LC) transitions at 288 nm and Ru-based moderate spin-allowed MLCT absorption between 440–450 nm. The Ru(μ-LL′)Os and Os(μ-LL′)Ru dinuclear complexes show Os-based unit absorption in the range of 565–583 nm. The Ru-based units of the complexes present different emission intensities due to differing steric hindrance at the coordination sites of the two bridging ligands. The Os(μ-LL′)Ru dinuclear complexes present weaker emission intensity than their parent monometallic complexes (μ-LL′)Ru. These results indicate that the emission of Os(μ-LL′)Ru dinuclear complexes is quenched by the Os(ii )-based units.